Partisan Priorities and Public Budgeting. (December 2014) - Epp, Derek A.; Lovett, John; Baumgartner, Frank R.
We explore budget data from twenty-nine Western countries from 1948 to 2012 to investigate the impact of partisan control of government on spending patterns. We use a variety of empirical methods, but the central element of analysis is to code spending allocations as "consistent" or "inconsistent" based on the partisanship of the majority party in government. Looking across the board, we show that inconsistent allocations occur at almost exactly the same rate as consistent ones. The implication is that budgets are best understood not as an expression of partisan priorities but as a reaction to changing contextual circumstances.